2022
DOI: 10.1002/jdd.12954
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception on flipped classroom in contrast to live demonstration for teaching orthodontic wire‐bending skills: A focus group study

Abstract: Objective: This study aimed to explore students' perceptions of flipped classroom (FC) compared to live demonstration (LD) in transferring skills of fabricating orthodontic wire components for orthodontic removable appliances.Methods: Forty third-year undergraduate dental students were randomly assigned to two groups: FC (n = 20) and LD (n = 20). Students in group FC attended FC, while students in group LD attended LD. Both groups underwent a series of standardized teaching sessions to acquire skills in fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A recent study emphasized the FC approach resulted in better student performance in five areas of clinical skills: intravenous catheterization (IV), IV blood collection, blood pressure measurement from the brachial artery, intramuscular injection into the ventrogluteal region, and urinary catheterization in women [ 20 ]. Another study exploring third-year undergraduate dental students fabricating orthodontic wire-bending skills also compared FC with the live demonstration (LD) approach, and concluded that the FC outperformed the LD approach in fostering personalized learning and improving the efficacy of physical class time, but LD was more advantageous than FC in allowing immediate question and answer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study emphasized the FC approach resulted in better student performance in five areas of clinical skills: intravenous catheterization (IV), IV blood collection, blood pressure measurement from the brachial artery, intramuscular injection into the ventrogluteal region, and urinary catheterization in women [ 20 ]. Another study exploring third-year undergraduate dental students fabricating orthodontic wire-bending skills also compared FC with the live demonstration (LD) approach, and concluded that the FC outperformed the LD approach in fostering personalized learning and improving the efficacy of physical class time, but LD was more advantageous than FC in allowing immediate question and answer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, students were unwilling to work at home as is typically done in a traditional face-to-face class, and considered watching the pre-class videos to be a time [ 22 ]. Fourthly, the FC approach did not allow students to ask questions and receive immediate answers [ 21 ]. Finally, the online video demonstration is 2D, thus limiting the accurate representation of an actual 3D demonstration.…”
Section: Discussionmentioning
confidence: 99%
“…These advancements, together with social media and video records, enable educators at all levels to flip their classes to accommodate dentistry students' demands. 25 A previous study contains comprehensive information regarding the course and its assessment of impact. 16 A point usually raised as a limiting point of distance learning concerns the adherence of dental students to the program, which can be hindered by the virtual environment and lack of interaction with colleagues and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The present study's course was based on active learning methodologies, and support material was made available weekly for reading before the activities. These advancements, together with social media and video records, enable educators at all levels to flip their classes to accommodate dentistry students' demands 25 . A previous study contains comprehensive information regarding the course and its assessment of impact 16 …”
Section: Discussionmentioning
confidence: 99%